Environmental Impacts Potential of Natural Gas Production Through Life Cycle Assessment - Afghani, Akmal Al; Pratama, Mochamad Adhiraga; Dahlan, Astryd Viandila (UI Scholars Hub, 2024)
Life cycle assessment (LCA) is a methodology used to evaluate potential environmental impacts in various industry sectors, including the oil and gas industry to quantify the environmental impacts and determine the processes that have significant impacts along their production cycle. This environmental impact study adheres to ISO 14040:2016 and 14044:2017 standards, using the ReCiPe methodology within a gate-to-gate scope to analyze potential environmental impacts of 1 MMSCFD natural gas production. The impact categories analyzed in this study are Global Warming Potential (GWP), Particulate Matter Formation (PM), Ozone Formation (OF), and Terrestrial Acidification (TA). The results of this study identified several activities and processes in production cycle that can be categorized as hotspots: (1) Emissions from the Waste Heat Boiler and Thermal Oxidizer process to oxidize acid and permeate gas, (2) Emissions from the electricity generator unit, (3) Emissions from the compressor unit, and (4) Emissions from flaring activities related to safety operations. The quantified impacts of each category are GWP (3,555 kg CO2-eq), PM (0.52 kg PM2.5-eq), OF (3.36 kg NOx-eq), and TA (1.72 kg SO2-eq). This study maps the environmental impacts of natural gas production cycle, helping to identify further improvements for reducing potential environmental impacts.